Functional implication of Dclk1 and Dclk1-expressing cells in cancer - Westphalen, C. Benedikt (Small GTPases, 2016)
Doublecortin like kinase protein 1 (Dclk1) is a microtubule-associated protein with C-terminal serine/threonine kinase domain. Originally designated Doublecortin and CaM kinase-like 1 protein (Dcamkl1) or KIAA0369, Dclk1 was first described as a marker for radial glia cells in the context of microtubule polymerization and neuronal migration, possibly contributing to early neurogenesis. Additionally, Dclk1 was proposed as a marker of quiescent gastrointestinal and pancreatic stem cells, but in recent years has been recognized as a marker for tuft cells in the gastrointestinal tract. While Dclk1+ tuft cells are now considered as niche or sensory cells in the normal gut, growing evidence supports a role for Dclk1 function in a variety of malignancies, modulating the activity of multiple key pathways, including Kras signaling. Here, we review the recent advances in understanding of the importance of Dclk1 function in tumorigenesis and cancer.